Contrast Induced Nephropathy and Long-term Renal Decline After Percutaneous Transluminal Angioplasty for Symptomatic Peripheral Arterial Disease. Issue 3 (March 2016) - Sigterman, T.A.; Krasznai, A.G.; Snoeijs, M.G.; Heijboer, R.; Schurink, G.W.H.; Bouwman, L.H.
Abstract : Objective/background: Administration of iodinated contrast media during endovascular procedures for peripheral arterial disease (PAD) may cause contrast induced nephropathy (CIN). The aim of the present study was to establish the incidence of CIN after these procedures and to study its association with long-term loss of kidney function, cardiovascular events, and death. Methods: Consecutive patients first presenting with symptomatic PAD (Rutherford classification II–VI) who were treated with an endovascular procedure were included in this prospective observational cohort study. CIN was defined as >25% increase of serum creatinine concentration from baseline at 5 days after the intervention. Results: Some 337 patients were included with a mean estimated glomerular filtration rate (eGFR) of 67 mL/minute. Thirteen percent (95% confidence interval [CI] 9–16) of these patients developed CIN after endovascular interventions for PAD. One year after treatment, eGFR was reduced by 12.4 mL/minute (95% CI 8.6–16.2) in patients with CIN compared with 6.2 mL/minute (95% CI 4.9–7.0) in patients without acute kidney injury ( p  < .01). After correction for potential confounders, CIN was associated with a 7.8 mL/minute (95% CI 4.5–11.0) reduction of eGFR at 1 year after endovascular intervention ( p  < .01). Furthermore, patients with CIN were at increased risk of long-term cardiovascular events and mortality. Conclusion: Exposure to iodinated contrast media during endovascular procedures for symptomatic PAD frequently results in CIN. Patients with CIN are at increased risk of long-term loss of renal function, cardiovascular events, and death.